2022
DOI: 10.1007/s11238-022-09887-8
|View full text |Cite
|
Sign up to set email alerts
|

Delegation based on cheap talk

Abstract: PERMISSIONShttps://www.springer.com/gp/open-access/publication-policies/self-archiving-policy Self-archiving for articles in subscription-based journalsSpringer journals' policy on preprint sharing.By signing the Copyright Transfer Statement you still retain substantial rights, such as self-archiving:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 42 publications
(51 reference statements)
0
3
0
Order By: Relevance
“…Many other papers investigate the role of vague language in other forms of cheap talk games, including asymmetric coordination games with private information [32], leaderfollower public goods games [33], delegation games [34], cheating games [35], three-player common interest context-dependent communication games [36], and real-world communication about intentions on a TV game show [37]. Like this paper, these papers found that subjects, given the choice, prefer imprecise messages to outright lies, and followers are too trusting of these messages.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many other papers investigate the role of vague language in other forms of cheap talk games, including asymmetric coordination games with private information [32], leaderfollower public goods games [33], delegation games [34], cheating games [35], three-player common interest context-dependent communication games [36], and real-world communication about intentions on a TV game show [37]. Like this paper, these papers found that subjects, given the choice, prefer imprecise messages to outright lies, and followers are too trusting of these messages.…”
Section: Introductionmentioning
confidence: 99%
“…Like this paper, these papers found that subjects, given the choice, prefer imprecise messages to outright lies, and followers are too trusting of these messages. In some, vagueness is beneficial either because it can mask incentives that, if known, would make an attractive equilibrium strategically unsustainable [32,33], because it makes information more credible [34], or because it enables more efficient communication of context-dependent information [36].…”
Section: Introductionmentioning
confidence: 99%
“…4The seminal work of Niederle and Vesterlund (2007) has led to thousands of citations and numerous studies utilizing the addition exercise to study a wide range of economic, business, and social science applications (see, e.g., Price 2012, Zhang and Bayer 2022). …”
mentioning
confidence: 99%